Pengembangan Video Animasi SEJATI untuk Meningkatkan Literasi Budaya dan Kewarganegaraan Siswa Sekolah Dasar - Dinda A’inun Afithakul Jannah; Novi Nitya Santi; Sutrisno Sahari (YASIN, 2026)
Although animated video learning media have been widely developed for elementary school education, studies specifically integrating the history of kingdoms in East Java with the strengthening of cultural and civic literacy remain limited. This study aimed to develop the SEJATI (Sejarah Kerajaan di Jawa Timur) animated video media that is valid, practical, and effective in improving the cultural and civic literacy of fourth-grade students at SDN Tarokan 2. The study employed a Research and Development (R&D) approach using the ADDIE model, which comprises the analysis, design, development, implementation, and evaluation stages. The research participants were fourth-grade students at SDN Tarokan 2, involving eight students in the small-scale trial and 25 students in the large-scale trial. Data were collected through observation, interviews, questionnaires, expert validation, and pretest–posttest assessments and were subsequently analyzed using quantitative descriptive analysis based on validation results, user responses, and N-Gain calculations. The results showed that the SEJATI animated video media achieved a validity level of 100% from the subject matter expert and 90% from the media expert, both of which were classified as highly valid. The practicality level based on the teacher’s response reached 100%, while students’ responses reached 93.75% in the small-scale trial and 96.8% in the large-scale trial. The effectiveness of the media was demonstrated by N-Gain scores of 0.70 in the small-scale trial and 0.76 in the large-scale trial, both of which were categorized as high. These findings indicate that the SEJATI animated video media is valid, practical, and effective as an alternative learning medium for Natural and Social Sciences (IPAS) to help students understand the history of kingdoms in East Java while strengthening their cultural and civic literacy. This study contributes to the development of technology-based learning media that integrate local history with cultural and civic literacy and provides practical implications for teachers and educational institutions in delivering engaging, contextual, and innovative learning.